2021
DOI: 10.1051/e3sconf/202123201018
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Use of Village Funds on Sustainable Agricultural Development

Abstract: The priority of the Village Fund is for the village development programs and activities. The relatively large value of Village Funds in Indonesia is expected to affect the welfare of village communities and also sustainable. The problem is that not all villages have the same level of development, so the management of village resources cannot be uniformed. The objective of this paper is to analyze the impact of the Village Fund, especially for agricultural development. The location of this study included three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Village funds as pro-equality and pro-job policies are less studied. Recent studies (Indraningsih et al 2021) showed that a village fund encourages the increased production and income of farmers, where production facilities and the transportation of crops is more accessible through the improvement of agricultural facilities and infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Village funds as pro-equality and pro-job policies are less studied. Recent studies (Indraningsih et al 2021) showed that a village fund encourages the increased production and income of farmers, where production facilities and the transportation of crops is more accessible through the improvement of agricultural facilities and infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Technically, transmigrants get convenience by selling commodities through middlemen, because the middlemen come directly to the transmigration location; however, this practice perpetuates the dependence of transmigrants on other parties with a weak bargaining positionn (Budi et al, 2021;Indraningsih et al, 2021). Transmigrants are trapped in market mechanisms and are subject to price decisions by middlemen.…”
Section: Results and Discussion 1 Ease Of Market Accessmentioning
confidence: 99%
“…The success and sustainability of the transmigration program is largely determined by the quality of the supporting factors which are the main pillars of the transmigration program and activities, namely ease of market access, access to information, and availability of transportation at transmigration locations (Indraningsih et al, 2021). The purpose of this study is to describe the ease of market access, access to information, and the availability of transmigrant transportation in farming in Banyuasin and Ogan Ilir Regencies, South Sumatra.…”
Section: Introductionmentioning
confidence: 99%
“…The community uses village roads to facilitate the mobilization of socio-economic activities. Other public facilities, such as agricultural roads for harvesting-produce distribution, are also focused on improving the village government's support of food security [1,2]. In addition, empowerment and development programs for rural communities are part of the government's attention in their goal of implementing human development and social culture in rural areas [3].…”
Section: Introductionmentioning
confidence: 99%